Increasing Goat Productivity Through the Improvement of Endogenous Secretion of Pregnant Hormones Using Follicle Stimulating Hormone - Andriyanto, Andriyanto; Manalu, W (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. Previous studies reported that the improvement of endogenous estrogen and progesterone secretions during gestation improved fetal prenatal growth, birth weight, mammary gland growth and development, milk production, litter size, pre- and post-weaning growths. An experiment was conducted to apply the improvement of endogenous secretion of pregnant hormones during pregnancy to increase goat productivity. Thirty-six female ettawah-cross does were divided into 2 groups. Group 1 (control: 18 does) included does without improvement of endogenous secretion of pregnant hormones and Group 2 (treatment: 18 does) included does with improvement of endogenous secretion of pregnant hormones using follicle stimulating hormones to stimulate super ovulation. The application of this technology increased total offspring born (control: 25 offspring; treatment: 42 offspring), average litter size (control: 1.88; treatment: 2.33), offspring birth weight (control: 2.85±0.50 kg; treatment: 3.82±0.40 kg), and does milk production (control: 1.36±0.34 L/does/day; treatment: 2.10±0.21 L/does/day). Offspring born to does with improved endogenous secretion of pregnant hormones had better weaning weight (control: 11.17±1.99 kg/offspring; treatment: 14.5±1.11 kg/offspring). At weaning period, does with improved endogenous secretion of pregnant hormones produced offspring with total weaning weight twice as heavy as control does (control: 189.9 kg; treatment: 403.6 kg). By a simple calculation of economic analysis, this technology application could increase gross revenue per does until weaning by Rp. 432.888,89. It was concluded that this technology is economically feasible to be applied in small-scale farm.Key Words: follicle stimulating hormone, pregnant hormones, endogenous secretion, super ovulation, ettawah-cross does